Another win for endothelial progenitor cells: Endothelial progenitor cell-derived conditioned medium promotes proliferation and exerts neuroprotection in cultured neuronal progenitor cells - Nadia Sadanandan; Stefano Di Santo; Hans Rudolf Widmer (Brain Circulation, 2019)
Progress in stem cell research demonstrates stem cells' potential for treating neurodegenerative diseases. Stem cells have proliferative/differentiative properties and produce a variety of paracrine factors that can potentially be used to regenerate nervous tissue. Previous studies have shown the positive regenerative effects of endothelial progenitor cells (EPCs), and thus, they may be used as a tool for regeneration. A study by Di Santo et al. explored whether EPC-derived conditioned medium (EPC-CM) promotes the survival of cultured striatal progenitor cells and attempted to find the paracrine factors and signaling pathways involved with EPC-CM's effects. The neuronal progenitor cells that were cultured with EPC-CM had much higher densities of GABA-immunoreactive (GABA-ir) neurons. It was shown that phosphatidylinositol-3-kinase/AKT and mitogen-activated protein kinase/ERK signaling pathways are involved in the proliferation of GABAergic neurons, as inhibition of these pathways decreased GABAergic densities. In addition, the results suggest that paracrine factors from EPC, both proteinaceous and lipidic, significantly elevated the viability and/or differentiation in the cultures. Importantly, it was found that EPC-CM provided neuroprotection against toxins from 3-nitropropionic acid. In sum, EPC-CM engendered proliferation and regeneration of the cultured striatal cells through paracrine factors and imparted neuroprotection. Furthermore, the effects of EPC-CM may generate a cell-free therapeutic strategy to address neurodegeneration.